All Patients with Diabetes Should Have Annual UACR Tests. Why is That So Hard?. Issue 1 (20th September 2016) - Willison, Alice; Tully, Vicki; Davey, Peter
Abstract : The urine albumin creatinine ratio (UACR) detects abnormal levels of protein in the urine and should be performed annually to detect kidney disease in patients with diabetes mellitus. UK national audits show that 25% of patients do not have annual tests and our data suggested that some patients had more than one test per year. Data from 20 patients showed that 55% had more than one UACR test per year, with a total of 19 unnecessary tests at an estimated cost of £20, 000 per year. However 20% had not had a UACR in the previous year, so unreliable testing was potentially causing harm as well as waste. Process mapping showed that having a UACR test depended on whether the patient brought a urine sample to the clinic. Most (72%) patients were unaware that the urine sample was used to detect kidney damage. We encountered barriers when finding a process to automate measures of reliability of UACR testing using computer protocol, and therefore created a patient information leaflet. The first version of the leaflet was too technical and several changes were suggested by patients. After reading the revised leaflet 99% of patients understood the reason for UACR testing and 64% felt more motivated to bring in urine samples. The phlebotomist disseminated the patient information leaflet with a median of 90% reliability for six consecutive clinics. The patient information leaflet has the potential to improve patient involvement in their care and to increase the number of patients who bring urine samples to the clinic. However, this could increase the number of unnecessary tests unless the process of test ordering is changed to ensure that UACR is only measured annually.